Use of systematic evidence maps within the US environmental protection agency (EPA) integrated risk information system (IRIS) program: Advancements to date and looking ahead. (November 2022) - Thayer, Kristina A.; Shaffer, Rachel M.; Angrish, Michelle; Arzuaga, Xabier; Carlson, Laura M.; Davis, Allen; Dishaw, Laura; Druwe, Ingrid; Gibbons, Catherine; Glenn, Barbara; Jones, Ryan; Kaiser, J. Phillip; et al.
Abstract: Systematic evidence maps (SEMs) are increasingly used to inform decision-making and risk management priority-setting and to serve as problem formulation tools to refine the focus of questions that get addressed in full systematic reviews. Within the U.S. Environmental Protection Agency (EPA) Office of Research and Development (ORD) Integrated Risk Information System (IRIS), SEMs have been used to inform data gaps, determine the need for updated assessments, inform assessment priorities, and inform development of study evaluation considerations, among other uses. Increased utilization of SEMs across the environmental health field has the potential to increase transparency and efficiency for data gathering, problem formulation, read-across, and evidence surveillance. Use of the SEM templates published in the companion text (Thayer et al.) can promote harmonization in the environmental health community and create more opportunities for sharing extracted content.